IMPLEMENTASI SUPERVISI PEMBELAJARAN MENDALAM SEBAGAI STRATEGI INOVATIF PENINGKATAN KUALITAS GURU DAN PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN - Faizal Fakhri; Santa Adiyanta; Agus Suroso (Pendidikan Vokasional Teknologi Otomotif, Universitas PGRI Yogyakarta, 2025)
This study aims to analyze the implementation of deep learning supervision at SMK Negeri 1 Karangawen as a strategy to enhance the quality of teaching and teacher professionalism. The study is grounded in the government’s policy on the adoption of the deep learning approach within the Merdeka Curriculum, which emphasizes the development of critical thinking, collaboration, and contextual understanding among students. A qualitative case study design was employed, involving 63 teachers across three vocational programs: Mechanical Engineering, Automotive Engineering, and Fashion Design. Data were collected through pre-teaching interviews, classroom observations, and post-teaching interviews to provide a comprehensive understanding of how deep learning supervision was implemented.The findings indicate that the supervision activities had a significant positive impact on improving the quality of instructional practices. A total of 52 teachers (82.5%) achieved an Excellent category, 8 teachers (12.7%) were rated Good, and 3 teachers (4.8%) were rated Fair, with none in the Poor category. The supervision process enhanced teachers’ abilities in planning, executing, and reflecting on deep learning-based instruction, while also fostering a culture of collaboration and reflective practice among educators.In conclusion, deep learning supervision effectively improves teacher professionalism and the quality of vocational education. The results of this study are expected to serve as a reference for developing more adaptive supervision models aligned with the demands of 21st-century learning in vocational schools. Keywords: Instructional supervision, deep learning, vocational education, teacher professionalism, vocational school